Questioning the evidence for Earth's oldest fossils. - Brasier, M; Green, O; Jephcoat, A; Kleppe, A; Van Kranendonk, M; Lindsay, J; Steele, A; Grassineau, N (2002)
Structures resembling remarkably preserved bacterial and cyanobacterial microfossils from about 3,465-million-year-old Apex cherts of the Warrawoona Group in Western Australia currently provide the oldest morphological evidence for life on Earth and have been taken to support an early beginning for oxygen-producing photosynthesis. Eleven species of filamentous prokaryote, distinguished by shape and geometry, have been put forward as meeting the criteria required of authentic Archaean microfossils, and contrast with other microfossils dismissed as either unreliable or unreproducible. These structures are nearly a billion years older than putative cyanobacterial biomarkers, genomic arguments for cyanobacteria, an oxygenic atmosphere and any comparably diverse suite of microfossils. Here we report new research on the type and re-collected material, involving mapping, optical and electron microscopy, digital image analysis, micro-Raman spectroscopy and other geochemical techniques. We reinterpret the purported microfossil-like structure as secondary artefacts formed from amorphous graphite within multiple generations of metalliferous hydrothermal vein chert and volcanic glass. Although there is no support for primary biological morphology, a Fischer--Tropsch-type synthesis of carbon compounds and carbon isotopic fractionation is inferred for one of the oldest known hydrothermal systems on Earth.